2013
DOI: 10.1136/annrheumdis-2013-eular.848
|View full text |Cite
|
Sign up to set email alerts
|

THU0320 New Parameters for Identifying Subclinical Atherosclerosis in Patients with Primary SjöGren’s Syndrome: A Pilot Study

Abstract: Background Clinical and biochemical data suggest that autoimmune diseases are associated with endothelial dysfunction and increased atherosclerosis. We have previously shown that asymmetric dimethylarginine (ADMA) levels and coronary flow reserve (CFR) are impaired in patients with early rheumatoid arthritis (1), but it is not known whether the same is true for patients with primary Sjögren’s syndrome (pSS). Objectives To investigate sub-clinical cardiovascular involvement in pSS patients by means of ADMA, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 0 publications
6
35
0
Order By: Relevance
“…There is only one study in particular that to our knowledge has investigated PWV in primary SS. Atzeni et al found significantly higher arterial stiffness in 22 primary SS patients as compared to an age-and sex-matched control group (n ϭ 22) (11). Although the results are similar to ours, our patients (only women) were significantly younger (mean Ϯ SD age 60 Ϯ 8 years versus 50 Ϯ 9 years), since patients ages Ͼ65 years were purposely excluded to minimize the strong effect of age on PWV and to avoid as much as possible age masking the effect of the disease itself.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is only one study in particular that to our knowledge has investigated PWV in primary SS. Atzeni et al found significantly higher arterial stiffness in 22 primary SS patients as compared to an age-and sex-matched control group (n ϭ 22) (11). Although the results are similar to ours, our patients (only women) were significantly younger (mean Ϯ SD age 60 Ϯ 8 years versus 50 Ϯ 9 years), since patients ages Ͼ65 years were purposely excluded to minimize the strong effect of age on PWV and to avoid as much as possible age masking the effect of the disease itself.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, the majority of the studies have observed an excess of atherosclerosis, despite using different methods. Therefore, endothelial dysfunction (11)(12)(13)(14), increased arterial stiffness (11), increased carotid intima-media thickening (CIMT) (9), and abnormal ankle brachial index (15) have been more or less consistently described in these patients. There is only one study in particular that to our knowledge has investigated PWV in primary SS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In pSS ADMA, right and left PWV and left cIMT resulted higher, whereas CFR resulted lower in comparison with normal subjects. In addition, despite left ventricular systolic and diastolic function being similar in pSS and controls, echocardiographic findings support the presence of myocardial alteration in the former (47)(48)(49)(50). Interestingly, not only the Framingham Risk Score (FRS) but also the SS damage index (SSDI) were independently associated with PWV (48).…”
Section: Reviewmentioning
confidence: 78%